2002
DOI: 10.1002/med.10029
|View full text |Cite
|
Sign up to set email alerts
|

Polymethylene tetraamine backbone as template for the development of biologically active polyamines

Abstract: The concept that polyamines may represent a universal template in the receptor recognition process is embodied in the design of ligands for different biological targets. As a matter of fact, the insertion of different pharmacophores onto the polymethylene tetraamine backbone can tune both affinity and selectivity for any given receptor. The application of this approach provided a prospect of modifying benextramine (1). structure to achieve specific recognition of muscarinic receptors that led to the discovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 102 publications
(137 reference statements)
0
14
0
Order By: Relevance
“…A potential way out of the dilemma, though not a simple way, is perhaps the design and synthesis of structural analogues which mimic polyamine functions, but have more selective binding affinities than the natural polyamines. Melchiorre and his colleagues [138] have demonstrated that it is in principle possible to modify the polyamine backbone, and to attach substituents in such a way to the polyamine structure that compounds are obtained, which bind selectively to certain membrane receptor proteins and enzymes. This approach should also be applicable to regulators of growth, to regulators of the cell cycle and to apoptotic factors.…”
Section: Resultsmentioning
confidence: 99%
“…A potential way out of the dilemma, though not a simple way, is perhaps the design and synthesis of structural analogues which mimic polyamine functions, but have more selective binding affinities than the natural polyamines. Melchiorre and his colleagues [138] have demonstrated that it is in principle possible to modify the polyamine backbone, and to attach substituents in such a way to the polyamine structure that compounds are obtained, which bind selectively to certain membrane receptor proteins and enzymes. This approach should also be applicable to regulators of growth, to regulators of the cell cycle and to apoptotic factors.…”
Section: Resultsmentioning
confidence: 99%
“…They have long been associated with cell growth and cancer, and continued to be molecules that hold fascination for biologists, chemists, molecular biologists and clinical researchers [39]. Polyamines may represent a universal template in the receptor recognition process [40]. Various polyamine Screening of compound libraries, including corporate libraries with large structural diversities and those with similar structures generated from combinatorial synthesis, is a powerful approach for developing RNA-binding compounds [32].…”
Section: Anti-tumor (Cancer) Agentsmentioning
confidence: 99%
“…All these results have constituted the premise for medicinal chemists to design a new class of dual-binding site inhibitors thatable to simultaneously interact with the two sites-might alleviate the cognitive deficit in AD and, more importantly, address the etiology of the disease. 24 -26 In view of early evidence that polyamineamides were versatile molecular scaffolds suitable for designing com- pounds able to recognize multiple protein targets, 27 we considered the possibility of modifying the structure of 1 to obtain a multi-target-directed ligand (MTDL). 28 In addition to the cholinergic properties, we aimed to add to caproctamine another activity beneficial for AD, such as the antioxidant property.…”
Section: Memoquin Design Strategymentioning
confidence: 99%